COVID-19 vaccination challenges: A mini-review - Zeinab Mohseni Afshar; Mohammad Barary; Rezvan Hosseinzadeh; Bardia Karim; Soheil Ebrahimpour; Kosar Nazary; Terence T. Sio; Mark J. M. Sullman; Kristin Carson-Chahhoud; Emaduddin Moudi; Arefeh Babazadeh (Taylor & Francis Group, 2022)
The emergence of SARS-CoV-2 has led to the infection of many people across the globe, over six million deaths, and has placed an unprecedented burden on public health worldwide. The pandemic has led to the high-speed development and production of vaccines against the COVID-19, as vaccines can end the pandemic. At the beginning of the program, vaccinations were initially targeted only at high-risk groups, such as the elderly, those with comorbidities, or healthcare workers. Although most of the mentioned populations have received the two recommended doses, limited resources have left many authorities with an effective vaccine undersupply. Therefore, policies have been implemented to manage the available doses of the vaccines more efficiently. As there is no universally agreed consensus on this topic, we discuss the different recommendations and guidelines regarding the time interval between the two vaccine doses and explain the different scenarios for applying the two doses.